Ectopic Overexpression of CsECR From Navel Orange Increases Cuticular Wax Accumulation in Tomato and Enhances Its Tolerance to Drought Stress - Liu, Dechun; Guo, Wenfang; Guo, Xinyue; Yang, Li; Hu, Wei; Kuang, Liuqing; Huang, Yingjie; Xie, Jingheng; Liu, Yong (Frontiers in plant science, 2022)
Drought stress often occurred in citrus to limit its growth, distribution, and fruit quality. Cuticular waxes play an important role in regulating plant tolerance to drought stress. Plant enoyl-CoA reductase (ECR) is involved in the biosynthesis of cuticular waxes and catalyzes the last step of very long-chain fatty acids (VLCFAs) elongation. In this study, a putative ECR gene, named CsECR , was cloned from “Newhall” navel orange. CsECR protein has high identities with other plant ECR proteins and contained a conserved NADP/NAD-binding motif and three conserved functional sites. The highest expression of CsECR was observed in leaves, followed by stems, flavedos, ovaries, juice sacs, stigmas, stamens, albedos, and petals. Besides, the expression of CsECR was significantly induced by PEG6000 and ABA treatments. Ectopic overexpression of CsECR increased the contents of total waxes and aliphatic wax fractions ( n -fatty acids, unsaturated fatty acids, n -alkanes, alkenes, iso-, and anteiso-alkanes) in the leaves and fruits of the transgenic tomato. Furthermore, ectopic overexpression of CsECR reduced the cuticle permeability in the leaves and fruits of the transgenic tomato and increased its tolerance to drought stress. Taken together, our results revealed that CsECR plays an important role in plant response to drought stresses by regulating cuticular wax biosynthesis.